Climate Crisis as a National Security Threat: Challenges and Strategies of Indonesia - Brandy Emerson Ridho (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Climate change has emerged as one of the most pressing and multifaceted threats to national security across the globe, including in Indonesia. The consequences of climate change extend far beyond environmental degradation, posing significant risks to critical sectors such as food security, water resources, social cohesion, and the overall stability of national defense systems. Rising temperatures, shifting precipitation patterns, and the increasing frequency of extreme weather events-such as floods, droughts, and storms-have direct and indirect impacts that undermine the resilience of communities and the functionality of state institutions. In Indonesia, a country characterized by its vast archipelago and diverse ecosystems, the climate crisis presents unique challenges. The vulnerability of coastal regions to sea-level rise threatens the livelihoods of millions, while disruptions in agricultural productivity jeopardize food availability and economic stability. Moreover, these environmental stresses exacerbate social inequalities and can trigger internal displacement, heightening the risk of social unrest and conflict. Such dynamics underscore the critical intersection between environmental changes and national security concerns.